Exploring a Last-Mile Solution in High Density Residential Neighborhood for Transit-Oriented Development - Kim, Chansung; Jin, Young-Goun; Park, Jiyoung (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study aims at introducing the last-mile transportation system in high density residential neighborhood and estimating impact of last-mile solution on system performance.Methods/Statistical analysis: The study utilized agent-based model such as multi-agent transport simulation (MATSim) tool. The effect of introducing the minibus assumed in this study was applied to the analysis of public transportation demand and minibus analysis module embedded in MATSim. The minibus module contributes to solving network design problem, estimating the public transport schedule based on fixed public transport demand, providing the number of vehicles needed and the necessary routes.Findings: This study applied one alternative to provide only minibus as a last mile solution to improve connectivity between land use and transportation. The other alternative was mixing strategy to supply not only new Bus Rapid Transit (BRT) to main trunk road, but also minibus to the high-density neighborhoods. The study area was Sejong City in Korea and was a new administrative capital city. In conclusion, the strategy of introducing the minibus was more effective, especially for applying the BRT to the main trunk road and introducing the minibus to the narrow branch road. The number of passengers, the number of routes and the number of vehicles using BRT and minibus were slightly different according to scenarios. Based on simple revenue and labor cost analysis, the feasibility analysis showed that it was effective to connect the BRT between the neighborhoods in the high-density neighborhood plan as in Korea and to put the minibus between the high-rise residential building and the residential building inside the neighborhood.Improvements/Applications: Future study suggests that expansion of the entire city of Sejong, consideration of competition between car, minibus and walk modes with different income groups be required.Â Â